Transitionen in der Erwachsenenbildung : gesellschaftliche, institutionelle und individuelle Übergänge - Schmidt-Lauff, Sabine; Felden, Heide von, 1955-; Pätzold, Henning (Schriftenreihe der Sektion Erwachsenenbildung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE)., 2015)
In view of social transitions, transitions are becoming an important topic of adult education research and professionalism. The authors show research contexts and practical references and explain important terms such as status passages, transitions, trajectories, coping with transitions, subject. Scientific approaches are theoretically and empirically clarified and pedagogical concepts of a learning-promoting accompaniment of transitions are presented.